2017
DOI: 10.1590/1981-52712015v41n3rb20170003
|View full text |Cite
|
Sign up to set email alerts
|

Medical Professionalism: the Effects of Sociodemographic Diversity and Curricular Organization on the Attitudinal Performance of Medical Students

Abstract: Introduction: Socioeconomic and demographic diversity in the educational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(43 reference statements)
1
5
0
1
Order By: Relevance
“…This result was consistent with higher scores on attitudes toward COVID-19 preparedness and attitudes toward career after graduation among religious students. This result resonates the result of previous research in Brazil showing high attitudinal score of religious students than non-religious students [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was consistent with higher scores on attitudes toward COVID-19 preparedness and attitudes toward career after graduation among religious students. This result resonates the result of previous research in Brazil showing high attitudinal score of religious students than non-religious students [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…Identifying factors affecting medical professionalism in medical students during public health crisis is imperative for advancing professionalism education within medical school. Notably, certain demographic characteristics—gender [ 10 ], socioeconomic status [ 11 ], religious affiliation [ 12 ]—have been noted to influence medical students’ perception of medical professionalism, warranting further investigation. Additionally, mental well-being of medical students was found crucial to maintain professional identity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MS1 group had the greatest agreement with patients regarding EPP (Table 4), especially compared with the MS4 group. Previous studies revealed lower professional attitude scores and less empathy associated with increasing years in medical school [31,32]. MS4s have more experience with sleep deprivation causing physical and mental exhaustion [33].…”
Section: Discussionmentioning
confidence: 97%
“…anunciada e transparente, perante a chefia e os pares. Já os sentimos dizem respeito à satisfação, à completude e à felicidade com o trabalho 28 , que podem ser percebidas pelo clima de harmonia que o profissional deixa transparecer ao realizar sua atividade laboral.…”
Section: Casuística E Métodosunclassified